Which companies among the SMEs operate in accordance with the Sustainable Development Goals - Węglarz, Magdalena; Ropuszyńska-Surma, Edyta; Zimmer, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The purpose of the article is to identify the factors that have a significant impact on the decision of SMEs to operate in accordance with the Sustainable Development Goals (SDGs). The identification was made on the basis of data collected in December 2022 during a survey of a sample of 303 SMEs from all over Poland. In order to identify the above-mentioned factors, the following were analyzed: type of business, industry to which the primary economic activity of the surveyed company is assigned, age of the company, type of ownership, scope of activity, organizational and legal form, number of employees, average annual net income. Correlation tests confirmed the hypotheses of the relationship between the number of employees and average annual net income and operation in accordance with the SDGs. Further verification of the relationship, performed using a logit model, confirmed that average annual net income and industry are significant variables. There is a relationship between these variables and acting in accordance with the SDGs. The chance of making a decision by a company about operating in accordance with the SDGs increases as the average annual net income increases. The probability of operating in accordance with the SDGs is higher if the company operates in the following industries, i.a.: real estate activities, transportation, financial and insurance, construction, agriculture.
Keywords: decision making; sustainable development; sustainable business model; SME; logit model